Sustainability Advocacy Antecedents: how Social Media Content Influences Sustainable Behaviours among Generation Z - Dyah Permata Sari; Adi Setiawan (International Journal of Business, Economics, and Social Development, 2026)
This study examines how sustainable habits and sustainable consumption behaviors influence the discussion of exposure to sustainability content on social media and the sustainability advocacy on social media. Data from 98 Generation Z respondents were collected using a Likert scale and analyzed using SmartPLS Version 4.0 using an associative quantitative approach. The results indicate that conversations about sustainability issues on social media have a significant influence on the development of sustainable lifestyles and sustainable consumption habits. Furthermore, the results indicate that both variables have a significant influence on commitment to sustainability on social media and Acting as an intermediary in this regard, this study confirms that to develop concrete behaviors and increase digital consumer engagement, it is crucial to consistently highlight sustainability issues on social media particularly in the empirical context of the coffee shop industry. Keywords: Sustainability Content, Sustainable Habits, Sustainable Consumption Behaviors, Sustainability Advocacy, Generation Z